A Complex Body of Filmmakers: The Socio-Technical Nature of Collaborative Expertise in Shooting Auteur's Film - Tuusa, Saara (Edições Universitárias Lusófonas, 2026)
No matter which disciplinary location, the figure of the auteur haunts theories of film authorship and filmmaking. This paper suggests reconnecting to the richness of filmmaking in everyday practice in order to “flesh out” what film authoring is. Based on two ethnographic case studies in the European independent film context, Sebastian (2024, dir. Mikko Mäkelä) and Raptures (2025, dir. Jon Blåhed), this paper examines what creative collaborative expertise looks like on auteur’s film sets. The data suggests that rather than by any single body, auteur’s film is produced by a complex socio-technical "plural subject" (Bacharach and Tollefsen, 2010) that I call the body of filmmakers. Yet, the “sufficient creative control” (Livingston, 2011) of director-screenwriters remains crucial, showing that auteurism is a part of the material, social and cultural processes of filmmaking. Consequently, the paper is a case in point for the value and necessity of engaging with filmmaking empirically in order to theorise it.